Elevated Temperature Effects on the Behavior of One-Way Fi-brous Reinforced Concrete Slabs - Mazin B. Abdul-Rahman, Dr.; Alya'a A. Al-attar, Dr.; M. Younus, Amenah (International Journal of Engineering and Technology, 2018)
In this research, the effect of elevated temperature on the flexural behavior of one-way reinforced concrete slabs under service static loads contain different volume fraction (0.25% , 0.75% and 1.25%) of steel fibers and different addition ratios (15%, 20% and 25%) of fly ash in addition to the reference slabs with not any additives  was studied. For this purpose, thirty cylinders (150 *300)mm , thirty prisms (100 * 100 * 500)mm and forty one-way slabs (900 * 350 * 70) mm were cast and tested. The one-way tested slabs were divided into two groups. The first group (of twenty slabs) were tested to determine the ultimate flexural strength under static loads at normal temperature. While the second group (of twenty slabs) were tested to determine the flexural behavior of slabs under static service loads at elevated temperature (using burning furnace). In this test, the samples are exposed to rising temperature reached 850℃. From these tests, the relationships between the load and  mid-span deflection as well as the relations between the  fire-time and mid-span deflection are measured. The results showed that the addition of steel fibers and fly ash particles will enhance the flexural behavior of concrete slabs. The highest increase in ultimate load compared to the reference slab was (28.31%) at the volume ratio 1.25% of the steel fibers and 25% of the fly ash at normal temperatures , And the rate of increase of the deflection with fire time was the lowest increase rate is 14.1% at the volume of 1.25% of steel fibers and the proportion of weight 20% of fly ash at high temperature.